2016
DOI: 10.1128/jcm.03036-15
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Operational Performance of Tuberculosis Detection by Loop-Mediated Isothermal Amplification Platform in Decentralized Settings: Results from a Multicenter Study

Abstract: Currently available nucleic acid amplification platforms for tuberculosis (TB) detection are not designed to be simple or inexpensive enough to implement in decentralized settings in countries with a high burden of disease. The loop-mediated isothermal amplification platform (LAMP) may change this. We conducted a study in adults with symptoms suggestive of TB in India, Uganda, and Peru to establish the feasibility of using TB-LAMP (Eiken Chemical Co.) in microscopy laboratories compared with using smear micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 11 publications
4
34
2
2
Order By: Relevance
“…Although the recognition of 6–8 independent target sequences (via 4–6 primers) suggests higher specificity and sensitivity than standard PCR, which uses only two primers, the increase in primers can also cause nonspecific amplification9. Compounding this problem is the fact that traditional methods of evaluating LAMP reactions cannot directly check for nonspecific amplification, among other issues.…”
mentioning
confidence: 99%
“…Although the recognition of 6–8 independent target sequences (via 4–6 primers) suggests higher specificity and sensitivity than standard PCR, which uses only two primers, the increase in primers can also cause nonspecific amplification9. Compounding this problem is the fact that traditional methods of evaluating LAMP reactions cannot directly check for nonspecific amplification, among other issues.…”
mentioning
confidence: 99%
“…This study shows that for active tuberculosis detection in routine, Sensitivity of TB-Lamp assay is higher than SSM. Previous studies conducted in differents setting have demonstrated that TB-Lamp assay has an excellent sensitivity for Tuberculose detection [10]- [15].…”
Section: Discussionmentioning
confidence: 99%
“…This method is dependent on autocycling strand displacement DNA synthesis performed by the Bst DNA polymerase large fragment which has high-strand displacement activity, and is carried out at 65˚C for 1 hour [9]. TB-Lamp assay seems well adapted for in low incomes countries [6] [10].…”
Section: Introductionmentioning
confidence: 99%
“…The unique property depends on the size and composition of the particles compared to atoms and other materials. These properties includes: (1) large to volume ratio (metal NP, in The sensitivity of TB-LAMP is lower than Xpert MTB/RIF assay but greater than smear microscopy (Gray et al 2016;Pham et al 2018) Recommended by WHO particular gold NP), (2) surface plasmon resonance, (3) Surface-Enhanced Raman Scattering (SERS), (4) super-magnetization or ferromagnetic nanoparticles (e.g. iron oxide), (5) enhanced photoluminescence (semiconductor quantum dots), (6) high electric and heat conductivity, (7) potent surface catalytic activity (Gatoo et al 2014;Khan et al 2019).…”
Section: Nanoparticlesmentioning
confidence: 99%